CHLORINE RESIDUALS IN WASTEWATER TREATMENT: IMPLICATIONS FOR PATHOGEN INACTIVATION AND ENVIRONMENTAL IMPACT - Paramerta, Ni Made Amanda Putri Paramerta; Nadhifah, Dinda Fairuz; Marques, Madalena G.J.V.; Saefurrahman, Farhan; Stephanie, Inna; Wikaningrum, Temmy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Chlorine residuals are a critical component of wastewater treatment systems. Inactivation of pathogens is a crucial goal to protect public health and stop the spread of waterborne illnesses. The purpose of this study is to find out more about the use of chlorination to dominate all pathogenic bacteria in a safe environment. The method used in this paper is an approach to literature review, which is carried out by publishing articles, including browsing the internet, Google Scholar, and related journals. The study highlights the importance of understanding the relationship between the chlorine doses given and the resulting concentration of the residuals. In addition, the study emphasizes the potential consequences of an ecosystem, such as excessive algae growth and the contribution of methane gas production to greenhouse effects. Our findings focus on the need for a comprehensive approach to managing chlorine residuals, considering aspects of health in humans, effective inactivation that is pathogenic, and preserving the environment for long-term sustainability.